IMPLMENTASI KEBIJAKAN ELEKTRONIC GOVERNMENT DI KPP PRATAMA MEULABOH - Cahyati, Ita; Tjoetra, Afrizal; Ikhsan, Ikhsan (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2020)
The aim of this study was to determine how electronic government is implemented to improve the quality of services in KPP Pratama Meulaboh, West Aceh Regency. The process of delivering services to the public is made simpler by implementing electronic government, which provides the community with the resources and information required. This study uses methods of qualitative research with a descriptive approach. It is quite good based on the results of the research carried out by the implementation of the electronic government in KPP Pratama Meulaboh. This can be seen from the existence of good communication within the scope of the KPP Pratama and to stakeholders (stakeholders), the overall adequate resources, the good behavior of policy makers and the bureaucratic structures that support the implementation of the electronic government.